Minat Beli Konsumen Ditinjau Dari Store Atmosphere, Product Assortment Dan Kepercayaan (Studi Kasus Pada Outlet Donatello Surakarta) - Frida Ria; Rochmi Widayanti; Sudarwati (JURNAL WIDYA GANECWARA, 2020)
The research aims to find out and describe the influence of simultaneously or partial store atmosphere, product assortment and trust towards consumer purchase interest in Donatello Surakarta. This methodology research using quantitative descriptive research. The population was all consumer Donatello Surakarta is 2574 people. The number of samples was determined with the formula Slovin and the result 100 respondents. Sampling method using convenience sampling. The questionnaire used for data retrieval. Data analysis technique used was statistic analysis is multiple linier regression, F test, t test and determination coefficient. This test results the store atmosphere, product assortment and trust simultaneously and significance effect on consumer purchase interest in Donatello Surakarta. Store atmosphere influential positive and significance effect against the consumer purchase interest in Donatello Surakarta. Product assortment influential positive and significance effect against the consumer purchase interest in Donatello Surakarta. Trust influential positive and significance effect against the consumer purchase interest in Donatello Surakarta. Keywords : Purchase Interest, Store Atmosphere, Product Assortment, Trust